Octave Mirbeau et les clivages du moi - Lair, Samuel (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2005)
Mirbeau's inner world, with its hidden treasures, its disorder, its constructive incoherence, creates a literature in its own image, violent, disparate and generous. His entire work is part of his contemporary Viennese master's one. Subconscious deliberate mistakes, sublimations, perversions, original scenes, neuroses... Everything leads the reader to integrate the biographical element into the very act of creation. The regressive attitude of his earlier novels which translates into a desire for fusion with Nature turns in the 1890s into a will of self-construction eventually opening onto a confident vitality and an enthusiastic belief in modernity. But this decadent literature, no more than a naturalistic one, should not be reduced to a psychoanalytic analysis. Should they exist, these elements are subjected to a literary transmutation which urges the reader to conceive his own personal myth rather than sense a neurotic divide. Torn between an intellectual demand and a spiritual expectation, it seems nonetheless that Nature, the element of inspiration for the author, lets us feel a prospective deep division.
Octave Mirbeau's rifts